(3JdNjU GdeNQhWGJ aj GdgfOSI dGHdhfjhSs - (3eMehO Hf bGSe Hf GdaVd GdCUHgGfjs; (3GjdhfjhSs ((3eMehO Hf eSYhO Hf GdeUdM (B((3GdTjQGRi(B) s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf, hGdUdGI hGdSdGe Ydi SjO GdeQSdjf s
(3BNQgG (B:s
(3haQZ ef EJeGeg hJMQjQg ai TghQ efg KdGK YTQI hNeSeGFI gLQjI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B30 (3Cs
(3eQJH Ydi SHY ebGdGJs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdQjGVjGJs